The CXCL12/CXCR4 Axis: An Emerging Therapeutic Target for Chronic Pain - Chen Z; Xia Y; Liu B; Fang J; Hu Q (Journal of Pain Research, 2025)
Zhangwei Chen, Yunfan Xia, Boyi Liu, Jianqiao Fang, Qimiao Hu The Third School of Clinical Medicine (School of Rehabilitation Medicine), Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Qimiao Hu, The Third School of Clinical Medicine (School of Rehabilitation Medicine), Zhejiang Chinese Medical University, 548 Binwen Road, Hangzhou, 310053, People’s Republic of China, Email 20211026@zcmu.edu.cnAbstract: Chronic pain greatly affects patients’ quality of life and poses significant challenges for the healthcare system. Conventional medication is generally inadequate for managing chronic pain and frequently leads to numerous adverse effects. The chemokine C-X-C motif ligand 12 (CXCL12) and its receptor, the chemokine C-X-C motif receptor 4 (CXCR4), are emerging as significant neuromodulators within the nervous system. A growing body of evidence has underscored the critical roles of this chemokine axis in the development and persistence of pathological pain. In this review, we aim to synthesize recent findings that highlight the role and mechanisms of the CXCL12/CXCR4 axis in the etiology of chronic pain conditions. We focus on chronic pain stemming from sciatic nerve injury, diabetic neuropathy, spinal cord injury, bone cancer, opioid tolerance, and opioid-induced hyperalgesia. These conditions represent a diverse range of pathologies that underscore the broad impact of the CXCL12/CXCR4 axis in pain management. Furthermore, we discuss the potential for targeting the CXCL12/CXCR4 axis as a comprehensive therapeutic strategy for chronic pain. In this review, we aim to summarize emerging evidence on the critical role of the CXCL12/CXCR4 signaling in mediating chronic pain pathogenesis and its potential contributions to neurological disorders.Keywords: CXCL12, CXCR4, chemokine, pain